Raul Castro’s reforms: an assessment of their reach and contents - Chaguaceda, Armando (2012)
The author analyses the recent reforms enacted by the Cuban government. The essay argues that the reforms seek for improving Cuba’s economy, as well as its gobernability, but the foreseen changes do not make room for the emergence of political actors other than the ruling party. However, the author thinks that a plurality of civil society actors should agree on a plan and modes of action that would open the door for the protection of the Cuban citizen’s rights vis-à-vis the State.